CYCLICAL CUSHING’S DISEASE WITH DISSEMINATED TUBERCULOSIS - Jie, Tan Ying; Voon, Tong Chin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Corticotroph adenomas account for the majority of cases of cyclical Cushing’s Syndrome (CS). We described a middle-aged female with cyclical Cushing’s Disease (CD) complicated with disseminated tuberculosis (TB) infections involving lymph nodes, the brain and the colon. CASE A 30-year-old Malay female presented with classical CS symptoms: weight gain of 10 kg, acne eruption, abdominal striae, proximal myopathy, and skin bruising. Her random 4 pm serum cortisol was 1003 nmol/l and 24-hour urine cortisol levels were elevated 3 times above the upper limit. However, a month later, her overnight dexamethasone test (ODST) was suppressed at 38.4 nmol/l with a serum ACTH of 1.8 pmol/L, and her symptoms had resolved. Three months later, she had a recurrence with an unsuppressed low-dose dexamethasone test and elevated 24-hour urine cortisol. She was diagnosed with cyclical CD following high serum ACTH level 20.5 pmol/L (1.6–13.9 pmol/L). Further testing was planned, but she was found to be pregnant. Her disease remained quiescent throughout her pregnancy. Postpartum, her CS symptoms and hypercortisolaemia recurred along with hypokalaemia and prediabetes, though her blood pressure was normal. Post-partum, she underwent total thyroidectomy and left central lymph node dissection for a suspicious thyroid nodule with thyrotoxicosis. Histopathology revealed left micropapillary thyroid carcinoma with chronic granulomatous changes in the lymph nodes, consistent with TB. Pituitary MRI revealed a pituitary microadenoma measuring 0.7 cm and a tuberculoma in the cerebellum. TB meningitis was confirmed after an MTB GeneXpert test was performed on her cerebrospinal (CSF) fluid and yielded a positive result. CT scan of the abdomen and pelvis showed features suggestive of TB in the gut, and a colonoscopy revealed multiple transmural ulcers with positive MTB PCR results. Anti-TB therapy was initiated, and a multidisciplinary meeting recommended pituitary surgery after the intensive phase of anti-TB therapy. CONCLUSION This case illustrates the complexities in managing CD which may be cyclical and further complicated with severe opportunistic infections.